Falls in anaemic and non-anaemic hospitalized elderly patients in 2012-2016 - mutual relationships - Weber, P; Weberova, D; Matejovska-Kubesova, H; Meluzinova, H; Jarkovsky, J; Bielakova, K; Hrubanova, J; Polcarova, V (Advances in gerontology, 2019)
Although falls are more prevalent as ageing proceeds, it cannot be assumed that they happen due to ageing alone. The retrospective cohort study of data was targeted to make an analysis of prevalence of falls in anaemic patients in comparison to the non-anaemic elderly admitted to the acute geriatric department and evaluation of pertinent influence of age, gender and immobility on occurrence of falls. During the considered period of four years (2012-2016) the authors treated 9 363 elderly patients aged 79,9±8,6 years (in the majority of them 65+ years). Among them there were 8 809 non-anaemic and subgroup of 551 old anaemic patients (aged 81±7 years) with decreased haemoglobin (<110 g/l). Falls at hospital admission in average was present in 1 766 non-anaemic persons (20%) in comparison to 380 falls among anaemic patients (68,6%). Prevalence in anaemic subgroup is statistically significant higher (p<0,005). Also relation between falls and age, ADL and MMSE test and mobility is highly statistically significant (p<0,001). Meaningfully higher is occurrence of repeated falls in the anaemic subgroup in comparison to the non-anaemic one (41,2 vs 1,7%). The occurrence of falls in female gender in comparison to men is statistically significant higher in non-anaemic patients, not in anaemic group. Authors emphasize that anaemia appears to us as significant risk factor for falls in the elderly.
Keywords: Female; Anemia; Prevalence; multi-morbidity; ženské pohlaví; falls; lidé; anaemia of chronich diseases; Aged, 80 and over; hospitalizace; old age; prevalence; retrospektivní studie; Male; Aged; Hospitalization; Accidental Falls; senioři nad 80 let; senioři; anemie; mužské pohlaví; anaemia; úrazy pádem; Retrospective Studies; Humans